Integration of Change Theory and Evidence-Based Policies for Equitable Welfare in Mountainous Papua, Indonesia - Meiyenti, Ira; Sudrajat, Ihwan; Yahya, Afif Syarifudin; Mualim, Wildan Maulana Assani; Bulan, Nur Sari (Universitas Teuku Umar, 2026)
This research aims to integrate population administration projections with the Theory of Change (ToC) and Evidence-Based Policy (EBP) frameworks to strengthen policy formulation for the equitable distribution of welfare across districts in Mountainous Papua Province. The research used mixed methods with a sequential explanatory design. In the quantitative phase, population, Human Development Index (HDI), and district-level education indicators are projected for the period 2025–2045 using arithmetic and exponential methods, and the results are then compared across eight districts. In the qualitative phase, the projection findings were interpreted to assess the feasibility of policy assumptions, identify intervention needs, and formulate evaluation mechanisms in the spatial context of Mountainous Papua, using ToC as a prospective analytical tool. The results showed variations in trajectories across districts and misalignments between population growth and HDI increases: Yahukimo is projected to have the largest population but the slowest increase in HDI, whereas Jayawijaya and Central Mamberamo show a stronger upward trend in HDI. Education projections indicate uneven progress and declining participation in vocational education, which contributes to the missing middle skill gap. These findings confirm the need to differentiate district-profile-based interventions and to strengthen monitoring as a policy feedback mechanism. It was concluded that equitable distribution of welfare in Mountainous Papua requires predictive planning and data-driven adaptive governance, with ToC–EBP as a framework to test causal logic, target interventions, and strengthen policy evaluation.